1992
DOI: 10.1002/j.1460-2075.1992.tb05292.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective extracellular release of cholera toxin B subunit by Escherichia coli: dissection of Neisseria Iga beta-mediated outer membrane transport.

Abstract: The C‐terminal domain (Iga beta) of the Neisseria IgA protease precursor is involved in the transport of covalently attached proteins across the outer membrane of Gram‐negative bacteria. We investigated outer membrane transport in Escherichia coli using fusion proteins consisting of an N‐terminal signal sequence for inner membrane transport, the Vibrio cholerae toxin B subunit (CtxB) as a passenger and Iga beta. The process probably involves two distinct steps: (i) integration of Iga beta into the outer membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
137
0
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(140 citation statements)
references
References 51 publications
1
137
0
2
Order By: Relevance
“…In the absence of an obvious external energy source, it has been proposed that the free energy released upon the folding of the passenger domain in the extracellular space might provide a driving force for efficient translocation across the OM (2,22). To test this hypothesis, we fused the CyaA RD (residues 1,006-1,680) to EspPΔ1, a previously characterized derivative of EspP that contains the last 116 aa of the passenger domain and the β-domain (16), to generate a chimera designated RD-EspPΔ1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of an obvious external energy source, it has been proposed that the free energy released upon the folding of the passenger domain in the extracellular space might provide a driving force for efficient translocation across the OM (2,22). To test this hypothesis, we fused the CyaA RD (residues 1,006-1,680) to EspPΔ1, a previously characterized derivative of EspP that contains the last 116 aa of the passenger domain and the β-domain (16), to generate a chimera designated RD-EspPΔ1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although protein translocation reactions generally require the input of external energy in the form of either ATP hydrolysis or a membrane potential, there is no ATP in the periplasm, electrochemical gradient across the OM, or obvious connection to the protonmotive force across the IM. To explain the energetics of autotransporter secretion it has been proposed that the progressive folding of small segments of the passenger domain in the extracellular space drives translocation forward while preventing retrograde movement into the periplasm (2,22). This vectorial folding model is supported by the finding that mutations that impair the folding of C-terminal segments of two different autotransporter passenger domains significantly reduce the efficiency of secretion (19,23).…”
mentioning
confidence: 99%
“…One model proposes that the AT passenger crosses the OM in an unfolded conformation through the central pore of its own ␤-barrel domain. Stepwise folding of the passenger C terminus on the cell surface could then be used to prevent the passenger from sliding back into the periplasm, effectively creating a Brownian ratchet to drive OM secretion (7)(8)(9)(10)(11). Consistent with this model, it has been shown that the passenger C terminus crosses the OM first (12).…”
mentioning
confidence: 85%
“…Originally, it was proposed that the secretion of the unfolded passenger domain occurs through the hydrophilic channel formed by the monomeric ␤-barrel and that a globular conformation was not compatible with this mode of translocation (252)(253)(254). In support of this hypothesis, a recent study has demonstrated the existence of an ion channel in the ␤-domain of BrkA with an average conductance of 3.0 nS in 1 M KCl (449).…”
Section: Autotransporter Secretion Pathway (Type Va)mentioning
confidence: 99%
“…Proteins bearing a Ploop motif are not always ATP-or GTP-binding proteins, and even proteins binding ATP or GTP do not always possess this motif (433,522). Subsequently, it was suggested that since autotransporters can be correctly targeted and exported in nonnative gram-negative bacterial backgrounds, e.g., gonococcal IgA1 protease in E. coli, no additional secretion function is required and thus the energy source driving translocation across the outer membrane is derived from the correct folding of the passenger domain on the bacterial cell surface (254). From the study by Veiga et al (510), where a nonnative singlechain antibody reporter passenger domain was used, it appeared unlikely that the folding of the passenger domain on the cell surface would provide the energy required for the translocation through the outer membrane.…”
Section: Autotransporter Secretion Pathway (Type Va)mentioning
confidence: 99%